Recontextualising NAPLAN: A functional analysis of evaluations in media texts - Bangga, Lungguh Ariang; Lukmana, Iwa (Universitas Pendidikan Indonesia, 2019)
This paper explores the recontexualisation of issues surrounding NAPLAN test in the media through the lens of Systemic Functional Linguistics. In particular, this paper considers interpersonal meanings shared by journalists or media regarding the construal of NAPLAN test in Australian context. To obtain a comprehensive view regarding the construal, Appraisal analysis is deployed. Two different texts about a controversy of NAPLAN test in Australia are selected to be analysed: a hard news story and a comment piece. In addition to text analysis, an image accompanying the hard news story and a cartoon relating to the controversy of NAPLAN test are analysed to find out the realisation of meanings across two semiotic modes (texts and images). The results suggest that there are distinct patterns of realisation of evaluative meanings in these two texts. On the one hand, the hard news story tends to use indirect evaluation of either judgment or appreciation when dealing with the issue. On the other hand, evaluative meanings shared throughout the comment piece tend to be direct, negatively evaluating NAPLAN test and the educational system pertinent to the testing policy. In terms of text-image relations, results of analyses suggest that both texts and images orient readers to align with shared values regarding the construal of the controversial NAPLAN test in the Australian context.